Semantic Web and Model-Driven Engineering - Parreiras, Fernando S (Wiley, 2012)
Integrates two powerful software approaches to dramatically enhance enterprise computing Based on the author's own course materials, this book takes enterprise computing to the next level by offering readers a tested and proven method for applying semantic web tools to model-driven software engineering. It integrates and takes advantage of the latest advances from such disciplines as ontologies, description logics, domain-specific modeling, model transformation, and ontology engineering. Before advancing to practical applications, Semantic Web and Model-Driven Engineering lays a foundation of fundamental concepts: Part I, Fundamentals, explains the concepts and technologies underlying model-driven engineering and ontologies, explaining the common bonds and the differences between these two paradigms. Part II, The TwoUse Approach, describes the TwoUse Toolkit, which is used to implement a software development approach that integrates model-driven software engineering and ontology technologies. Part III, Applications in Model-Driven Engineering, features case studies that apply the TwoUse Toolkit to support software design patterns, ontology-based information systems, and the integration of software languages. Part IV, Applications in the Semantic Web, demonstrates and analyzes the author's integrated approach to ontology engineering. Throughout the text, tables summarize important data. In addition, detailed figures simplify complex programming and software engineering concepts and processes. Semantic Web and Model-Driven Engineering is ideal for all software engineers and students, giving them a new set of tools to dramatically enhance enterprise computing by lowering costs, raising productivity, and improving the quality of knowledge management, systems interoperability, and applications integration.